The role of modality in the realization of the author’s pragmatic attitude in a publicistic discourse - Akhramenko, Liubov S. (Journal of the Belarusian State University. Philology, 2021)
The article is devoted to the consideration of modality as the main text-forming factor based on the example of a publicistic discourse. The scientific novelty of the article lies in the identification of the multilevel (lexical, syntactic, compositional) peripheral means of the text modality, contributing to the indirect conviction of the addressee in the correctness of the author’s viewpoint. The pragmatic functions of the text modality have been determined, among which the most significant are increasing concept relevance and statement reliability, the formation of a presupposition for the perception of subsequent information. Modal dominants, typical for the prevailing types of modality typical of certain text parts – are revealed: motivational modality – for the introductory text part, cognitive modality, typical for the main text part, impositive modality, typical for the final text part. The motivational modality stimulates the addressee to the further text reading by increasing the relevance of the key text concept. Cognitive modality contributes to the intensification of the key concept significance through information. The impositive modality urges the addressee upon the correctness of the author’s viewpoint. The aforesaid modal dominants are the factors in the implementation of intermediate pragmatic attitudes in the introductory, main and final text parts respectively.